Regeneration Status of Important Tree Species in Achanakmar-Amarkantak Biosphere Reserve Due to the Extraction of Selected Non-timber forest Products - Bhat, Shabir Ahmad; Tiwari, Subhash Chandra (Indian Forester, 2012)
The species composition, dominance and regeneration status of tree species were studied in two blocks of Achanakmar-Amarkantak Biosphere Reserve (AABR) namely [Block II (Periphery) and Block I (Interior)].The tree density, sapling density and seedling density was higher in Block I as compared to Block II. In both blocks, GHB (Girth at breast height) showed decline in density from small girth class to higher girth class. The study also revealed the nature of changes effected on the character and composition of the biosphere reserve as a result of increasing anthropogenic disturbance and simultaneous changes in microclimate particularly in block I. As far as the regeneration status is concerned, maximum tree species was found with fair regeneration in the [Block I (Interior) than Block II (Periphery)] of the AABR. Meanwhile, in block II, nine species, while as in block I four species were not regenerated. There was lower species richness, species diversity, and mean height of trees in the block II which is a disturbed site, when compared with Block I the undisturbed sites. The seedling density and regeneration of plants were also lower in the disturbed site. Very few of the species extracted by villagers regenerated in the disturbed sites. This suggests that NTFP extraction is non-sustainable within the protected area and will eventually lead to loss of biodiversity and degradation of the forest.